Rosmarinic acid ameliorates acetaminophen-induced acute liver injury in mice via RACK1/TNF-α mediated antioxidant effect - Yang Yu; Yao Wu; Hao-zheng Yan; Zi-ru Xia; Wen Wen; Dan-yang Liu; Li-hong Wan (Taylor & Francis Group, 2021)
Context Rosmarinic acid (RA) dose-dependently ameliorates acetaminophen (APAP) induced hepatotoxicity in rats. However, whether RA hepatoprotective effect is by regulating RACK1 and its downstream signals is still unclear. Objective This study explores the RA protective effect on APAP-induced ALI and its mechanism. Materials and methods Sixty Kunming mice 6-8 weeks old were randomly separated into six groups (n = 10) and pre-treated with normal saline, ammonium glycyrrhetate (AG) or RA (10, 20 or 40 mg/kg i.p./day) for two consecutive weeks. Then, APAP (300 mg/kg, i.g.) was administrated to induce ALI, except for the control. Serum alanine/aspartate aminotransferases (ALT and AST), malondialdehyde (MDA), superoxide dismutase (SOD) and histopathology were used to authenticate RA effect. The liver RACK1 and TNF-α were measured by western blot. Results Compared with the APAP group, different dosages RA significantly decreased ALT (52.09 ± 7.98, 55.13 ± 10.19, 65.08 ± 27.61 U/L, p < 0.05), AST (114.78 ± 19.87, 115.29 ± 31.91, 101.78 ± 21.85 U/L, p < 0.05), MDA (2.37 ± 0.87, 2.13 ± 0.87, 1.86 ± 0.39 nmol/mg, p < 0.01) and increased SOD (306.178 ± 90.80, 459.21 ± 58.54, 444.01 ± 78.09 U/mg, p < 0.05). With increasing doses of RA, RACK1 and TNF-α expression decreased. Moreover, the RACK1 and TNF-α levels were positively correlated with MDA (r = 0.8453 and r = 0.9391, p < 0.01). Discussion and conclusions Our findings support RA as a hepatoprotective agent to improve APAP-induced ALI and the antioxidant effect mediated through RACK1/TNF-α pathway.